2021
DOI: 10.3389/fpsyg.2021.679904
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and Impulsivity in Young Adult Cannabis Users

Abstract: Aims: Chronic cannabis users show impairments on laboratory measures of decision making which reflect risk factors for initiation and continued use of cannabis. However, the differential sensitivity of these tasks to cannabis use has not been established. Moreover, studies to date have often lacked assessment of psychiatric histories and use of other illicit substances, both of which may influence decision making outcomes. The current study aimed to address these limitations by (1) including multiple types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Although in this study we did not evaluate the predictive validity of the model by testing anti-compulsive and/or anxiolytic drugs, our previous investigations (Pintori et al 2021) and the phenotypes observed in the nestlet shredding test indicate that the heightened marble burying activity of JWH-018treated mice likely reflects repetitive/compulsive-like rather than anxiety-like states. Previous studies have reported that chronic use of Cannabis is associated with increased risk-taking as well as impulsive behavior and poor inhibitory control (Lane et al 2005;Wrege et al 2014), both in adolescent and young adult individuals (Claus et al 2018;O'Donnell et al 2021). To evaluate the risk propensity of JWH-018 exposed mice, we tested them on the wire-beam bridge, a reliable test able to assess risk-taking behavior in both rats and mice, and particularly susceptible to pharmacological manipulations of the dopamine (Bortolato et al 2009;Frau et al 2017;Frau et al 2019;Festucci et al 2021) and cannabinoid systems (Frau et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although in this study we did not evaluate the predictive validity of the model by testing anti-compulsive and/or anxiolytic drugs, our previous investigations (Pintori et al 2021) and the phenotypes observed in the nestlet shredding test indicate that the heightened marble burying activity of JWH-018treated mice likely reflects repetitive/compulsive-like rather than anxiety-like states. Previous studies have reported that chronic use of Cannabis is associated with increased risk-taking as well as impulsive behavior and poor inhibitory control (Lane et al 2005;Wrege et al 2014), both in adolescent and young adult individuals (Claus et al 2018;O'Donnell et al 2021). To evaluate the risk propensity of JWH-018 exposed mice, we tested them on the wire-beam bridge, a reliable test able to assess risk-taking behavior in both rats and mice, and particularly susceptible to pharmacological manipulations of the dopamine (Bortolato et al 2009;Frau et al 2017;Frau et al 2019;Festucci et al 2021) and cannabinoid systems (Frau et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies indicated that impulsivity is not directly associated with problematic cannabis use [ 30 ], others suggested that impulsivity may instead be a distal factor in the cannabis–suicide relationship, contributing to the development of suicidal ideation but not the transition from ideation to attempt [ 7 ]. Yet, evidence of exacerbated impulsivity has been consistently linked with problematic cannabis use [ 32 ] and might mediate the transition from SI to SA [ 33 ]. The processes leading to impulsivity could be attributed to several factors, including stressor-provoked neurochemical changes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed a battery of assessments including the Structured Clinical Interview for DSM-IV-TR (SCID-IV-TR), Research Version [ 28 ]; a written drug use questionnaire [ 29 , 30 ]; a six-month timeline follow back assessment to estimate current and past use of CB and alcohol; the short Michigan alcohol screening test (SMAST); and the Wechsler Abbreviated Scale of Intelligence (WASI [ 31 ]). The control subjects had no history of substance dependence, a negative urine screen for CB and other substances, and no use of CB in the past three months.…”
Section: Methodsmentioning
confidence: 99%